Green synthesis, characterization and laser irradiation of silver nanoparticles and its bimetallic nanoparticles - Saleh Mubarak, Salah (2020)
Green synthesis of metallic nanoparticles offered an alternative and eco-friendly method for fabricating nanoparticles compared to chemical and physical methods. The current study aimed to manipulate silver nanoparticles (Ag NPs) synthesized in Murraya koenigii leaf extract to fabricate nanostructure by using diode laser irradiation. The green synthesized silver nanoparticles (Gre-Ag NPs) used as reducing and stabilizing agent to synthesize silver/copper nanoparticles (Ag/Cu NPs). The Ag NPs was synthesized by mixing Silver nitrate solution (AgNO3) (1, 3 and 5 mM) with M. koenigii leaf extract at room temperature and left for two days. In contrast, Ag/Cu NPs were synthesized by mixing Cu solution (1, 3, 5 and 7 mM) with Gre-Ag NPs at room temperature and left for 10 mins. Moreover, the silver nanostructures (Ag NSs) was fabricated by manipulating Gre-Ag NPs with diode laser 450 nm at different times. The Gre-Ag NPs, Ag/Cu NPs and Ag NSs were characterized by advanced analysis Ultra-Violent Visible (UV-Vis), Fourier transform infra-red (FTIR), X-Ray diffraction (XRD), Field emission scanning electron microscope (FESEM) and Atomic Force Microscopy (AFM). UV-Vis analysis showed peaks ranging from (426 to 441 nm) indicating AgNPs formation, as well as the absorbance at 512 nm to indicate the formation of Ag/CuNPs, in addition to a decrease in the absorbance when converting the silver nanoparticles into nanostructures. As for the FTIR, the results showed absorbing peaks for both M. konigii extract and AgNPs to indicate that the amino and carboxylic groups are responsible for the formation of AgNPs. The results of FESEM revealed that the Gre-Ag NPs have a spherical shape with diameter parameters between 10 and 80 nm, and XRD appeared that the Gre-Ag NPs have crystalline properties. The silver nanoparticles after being manipulated by diode laser irradiation for different exposure times are deformed into nanostructures as nano prisms, nanocone and nanohexagon examined by FESEM. Preparing metallic nanoparticles using the green method and manipulating them by diode laser irradiation is a simple and easy way to obtain different nanostructures.